2009
DOI: 10.1002/hup.1029
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia—pathways and neurotransmitters

Abstract: Fibromyalgia is a syndrome of widespread chronic pain associated with sleep disorders, depressed mood, cognitive impairment and fatigue. Its etiology and pharmacopathology are poorly understood but it is thought to result from a dysfunction of central pain processing mechanisms leading to generalised pain sensitisation. Pain perception is the result of a bidirectional process of ascending and descending pathways. Nociceptive input from peripheral afferent neurons is sent via the dorsal horn of the spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
1
37
0
8
Order By: Relevance
“…In addition, research studies over the past 20 years have shown that FMS is a pain amplification disorder with clear evidence for a pathogenesis within the central nervous system [10,11]. For example, in ours and other studies, it has been reported that there were elevated levels of substance P and nerve growth factor in the cerebrospinal fluid (CSF) of patients with FMS [7,12,13].…”
Section: Introductionmentioning
confidence: 84%
“…In addition, research studies over the past 20 years have shown that FMS is a pain amplification disorder with clear evidence for a pathogenesis within the central nervous system [10,11]. For example, in ours and other studies, it has been reported that there were elevated levels of substance P and nerve growth factor in the cerebrospinal fluid (CSF) of patients with FMS [7,12,13].…”
Section: Introductionmentioning
confidence: 84%
“…Hastalığın etyolojisi ve farmakopatolojisi yeterince anlaşılamamıştır. Ağrının santral modulasyonu ile inen inhibitör sistemde bozukluk ve substans P hiperaktivitesini ile açıklanmaktadır 6 . Santral ağrı yolaklarının disfonksiyonunun yol açtığı jeneralize ağrı sensitizasyonundan kaynaklandığı düşünülmektedir.…”
Section: Fibromiyalji Etyopatogeneziunclassified
“…Amerikan Romatizma Savaş (ACR) Derneği Sınıflama Kriterlerine göre diğer bölgelere kıyasla daha ağrılı bulunan 18 tipik hassas nokta kabul edilmiştir. Sınıflama amaçlı her iki kriteri de karşılıyor olması gereklidir 6,7,8,10 .…”
Section: Fibromiyaljide Klinik Bulgularunclassified
See 1 more Smart Citation
“…15 Dysfunction in these descending pathways is thought to result in the hyperalgesic (heightened sensitivity to pain) and allodynic (painful response to nonpainful stimuli) states experienced by patients with FM and other related central sensitization syndromes such as IBS and TMD. 16,17 The potential benefit of milnacipran in the treatment of FM was further supported by analgesic effects of SNRIs in animal models of pain, 18 as well as findings showing decreased cerebrospinal fluid levels of serotonin and norepinephrine metabolites in patients with FM. 19 Moreover, therapeutic benefits in FM had already been observed with drugs that inhibit the reuptake of both serotonin and norepinephrine, such as the TCA, amitriptyline.…”
Section: Introductionmentioning
confidence: 95%